Pelanggaran Maksim Kesantunan Berbahasa pada Novel “Teruslah Bodoh Jangan Pintar” Karya Tere Liye - Maghfiroh, Hayatin Nur; Tarmini, Wini (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to describe the forms of violations of language politeness maxims found in the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye. The method used is a qualitative research approach. Data collection techniques use listening and note-taking techniques. The results of the research showed that violations were found in the maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility, maxim of agreement, and maxim of sympathy. The most dominant violation is the violation of the maxim of praise. This is because this novel has complicated problems and is full of sentiment and the differences in thought patterns and differences in the social strata of the characters make one party feel superior to the other party so that the speaker easily demeans the person he is speaking to. The implication of this research is that the characters' speech can provide an illustration for readers regarding violations of language politeness maxims based on Leech's theory.